SISTEM KREDIT DALAM SHOPEE PAYLATER PERSPEKTIF HADIS - Aprilina; Muhajirin; Hedhri Nadhiran (CV DOKI COURSE AND TRAINING, 2023)
This article aims to examine the credit system in Shopee Paylater from a hadith perspective. Shopee Paylater is one of the payment methods in the shopee application with using a bailout or loan funds from shopee. The method of refunding is by installments or credit in every month and with a predetermined time. Each fund used has an excess price of 2,95% of the amount. In that case there are two opinions about Shopee Paylater, some are of the opinion that Shopee Paylater is prohibited because there is an excess price, and the excess price is usury. But there are some who think it is allowed because the Shopee Paylater system has an agreement between shopee and the user. Therefore, it is interesting to examine how the hadith views about Shopee Paylater. This type of research is library and qualitative research. The main data sources used are Sahih al-Bukhari, Sunan Tirmidhi, and Sunan Abi Dawud. Then, the data is analyzed with using descriptive analysis techniques through the ma'anil hadith approach. The results conclude that in the perspective of hadith the Shopee Paylater credit system is allowed, because the terms, conditions, and rhe Shopee Paylater credit system are clear. There is no sense of compulsion and mutually beneficial to each other.